Clinical History and Colliquative Myocytolysis Are Keys to the Diagnosis of Shoshin Beriberi. (7th May 2014) - Kuno, Toshiki; Nakamura, Hiroshi; Endo, Yutaka; Saito, Kohei; Yamazaki, Hiroyuki; Motoda, Hiroyuki; Numasawa, Yohei; Shimizu, Kazuhiko; Takahashi, Toshiyuki
Abstract : Cardiovascular beriberi presents as either the fulminant (Shoshin beriberi) or chronic form. Shoshin beriberi is a rare disease that may lead to a fatal outcome if the patient does not receive appropriate treatment. In the present report, we describe the case of a 66-year-old man presenting with leg edema and dyspnea at rest. Clinical presentations were nonalcoholic Shoshin beriberi and lactate accumulation; however, clinical improvement was observed after the administration of thiamine. His pretherapy thiamine level (2.1  μ g/dL) was consistent with a diagnosis of beriberi. Based on the findings of the present case, we believe that a diagnosis can be made in patients with a clinical history that is consistent with that of Shoshin beriberi, combined with low thiamine levels, lactate accumulation, and colliquative myocytolysis. Learning Objective. Shoshin beriberi is often misdiagnosed because of its rarity; a detailed clinical history and characteristic myocardial histopathology changes may be useful for making a definite diagnosis.